Indonesia Public Service Reform: Innovation Through Bureaucratic Entrepreneurship - Rina Herawati, Augustin; Eda Pradana, Azaria; Mior Shariffuddin, Nur Shahira (Indonesian Association for Public Administration (IAPA), 2024)
This study examines the Indonesia Serving Movement (Gerakan Indonesia Melayani or GIM) as a bureaucratic reform initiative aimed at improving public service delivery through the application of bureaucratic entrepreneurship strategies. GIM is part of the broader Gerakan Nasional Revolusi Mental (GNRM) and focuses on implementing innovation, efficiency, and accountability within Indonesia's public sector. GNRM was introduced to promote progress and modernity in Indonesia by implementing a culture of integrity, hard work, and communal cooperation. The literature review method was employed to analyze existing theoretical frameworks, including street-level bureaucracy and bureaucratic entrepreneurship, and to synthesize key findings on the role of public servants and managers in reforming service delivery. The study reveals that GIM has been successful in integrating e-government systems, establishing Public Service Malls (MPP), and implementing performance-based management. Despite its achievements, the study highlights challenges such as regional disparities and the limited availability of GIM-specific research. Recommendations for policymakers include strengthening bureaucratic entrepreneurship, expanding MPPs, and addressing regional inequalities.